Implementation of Quality Management System in the Department of Public Works and Highways - Malibong, Mark John B. (Philippine Social Science Journal)
The construction industry has been criticized for its poor performance and productivity. This study assessed the implementation of the quality management system provided by the quality assurance section of the Department of Public Works and Highways (DPWH) in Negros Occidental, Philippines. Using a descriptive, comparative, and correlational research design, data were collected using a researcher-made questionnaire accomplished by 265 respondents identified through stratified random sampling. Using descriptive and inferential statistics, findings showed a great extent of implementation, and clients and end-users revealed a high level of satisfaction. There was a significant difference in materials testing, quality assurance, and quality control. No significant difference was found in the level of satisfaction and between implementation and satisfaction on the implementation of the quality management system. The major challenge identified by implementers was responsibility. Indeed, the success of a quality management system requires proper monitoring and control.